The effect of chitosan nanoparticles on Escherichia coli viability in drinking water disinfection. Issue 2 (9th February 2022) - Denisova, V.; Mezule, L.; Juhna, T.
Abstract: Drinking water disinfection or inactivation of pathogenic microorganisms is an essential step to minimize infection risks and decrease the incidence of waterborne diseases. Recently, chitosan nanoparticles (CNs) have been highlighted as an antimicrobial agent for a wide range of applications due to their natural antimicrobial properties, and low or no toxicity risk for human health. In this study, we generated CNs from three different molecular weight (MW) chitosan (low, medium, high) at various concentrations (0.25, 0.5 and 2% (w/v)). After the CNs preparation and quality assessment, the antimicrobial activity was evaluated by measuring the log reduction of Gram-negative bacteria E. coli as a model microorganism for faecal pollution. The results demonstrated that 0.25% of medium MW CNs are optimal for more than 99.99% reduction of cultivable E. coli and 97% inactivation of metabolically active E. coli . These results indicated that CNs were able to inhibit the growth of cultivable and metabolically active E. coli in tap water and demonstrated the potential use of CNs as an alternative antimicrobial agent in drinking water disinfection. HIGHLIGHTS: CNs were synthesized by an ionic gelation method. MMWC with a chitosan concentration of 0.25% is the the most suitable material for bacterial inactivation. In drinking water, chitosan nanoparticles inhibit both cultivable and metabolically active E. coli . Graphical Abstract